"How Can a Student with Severe Disabilities Be in a Fifth-Grade Class When He Can't Do Fifth-Grade Level Work?" Misapplying the Least Restrictive Environment. (March 2020) - Giangreco, Michael F.
This article briefly responds to the following question: Why aren't more students with severe disabilities being placed in general education classrooms? I offer five reasons why more students with severe disabilities are not included, because: (a) ableism persists, (b) schools continue to misapply the least restrictive environment provisions of the Individuals with Disabilities Education Act in placement determinations, (c) too many team members have difficulty conceptualizing curricular inclusion, (d) some professionals pit placement against instruction as an "either/or" proposition, and (e) typical approaches to systems change leave behind students with severe disabilities. The article calls on the field to continue and speed the change process so that more students can benefit sooner from inclusive schooling.